Utilization of Daker (Buffalo Dadih) as A Natural Mask to Prevent Acne and Brighten The Face - Dihan Kurnia; Delli Lefiana; Devi Kumala Sari (Jurnal Ternak : Jurnal Ilmiah Fakultas Peternakan Universitas Islam Lamongan, 2023)
This study aims to determine the effect of adding coffee and tea powder to the quality of mask products from buffalo dadih. This study was conducted in the quality control laboratory of Payakumbuh State Agricultural Polytechnic University from July 16 to September 15, 2022.Â  The mask is made with a dilution using 1:1 aquadest. Furthermore, the daker was added with 5% coffee and tea powder, with the following treatment MD0 mask without the addition of coffee and tea, MD1 5% coffee powder addition, MD2 5% tea powder addition. Analysis of the quality of Daker masks: antioxidant activity, inhibition and growth of acne bacteria, And pH value. This study's results indicate that adding coffee and tea powder has antioxidants ranging from 29.93-55.60 ppm. This Buffalo dadih (DAKER) mask has a pH between 5.33-5.44 which does not irritate the skin. At the same time, this curd mask has an inhibition range from 10.00-11.23 mm. The addition of coffee and tea powder did not significantly affect the resistance of P. acne bacteria and pH but increased the antioxidant activity value of the DAKER mask.